Measurement of plasma density formed at passing of a sequeence of relativistic electron bunches through the neutral gas - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I.; Ivanov, B.I.; Prishchepov, V.P. (Вопросы атомной науки и техники, 2013)
Using an open barrel-shaped resonator (OBR) plasma density, produced by a sequence of duration 2 μs of relativistic electron bunches, each of energy 4.5 MeV and charge 0.16 nC, in air at pressure of 10…60 Torr was measured. The plasma density was determined from the shift of the OBR resonant frequency estimated after measuring the reduction of oscillations amplitude in plasma loaded OBR at the initial frequency of OBR. It was shown that the maximum density of the produced plasma reaches 3·10¹⁰ cm⁻³ at wakefield excitation in a semi-infinite plasma waveguide and 10¹¹ – in plasma resonator С помощью открытого бочкообразного резонатора (ОБР) измерена плотность плазмы, образуемая последовательностью релятивистских электронных сгустков длительностью 2 мкс, с энергией 4.5 MэВ, зарядом 0.16 нК каждого в воздухе с давлением 10...60 Торр. Плотность плазмы определялась по сдвигу резонансной частоты ОБР, оцененного по измерению уменьшения амплитуды колебаний в нагруженном плазмой ОБР на исходной резонансной частоте ОБР. Показано, что максимальная плотность образуемой плазмы достигает 3·10¹⁰cм⁻³ для возбуждения кильватерного поля в полуоткрытом волноводе и 10¹¹ см⁻³ – в плазменном резонаторе. За допомогою відкритого бочкоподібного резонатора (ВБР) виміряна густина плазми, яка утворюється послідовністю релятивістських електронних згустків тривалістю 2 мкс, з енергією 4.5 МеВ, зарядом 0.16 нК кожного в повітрі з тиском 10...60 Торр. Густина плазми визначалася по зсуву резонансної частоти ВБР, яка оцінювалася по вимірюванню зменшення амплітуди коливань у навантаженому плазмою ВБР на вихідній резонансній частоті ВБР. Показано, що максимальна густина утворюваної плазми досягає 3·10¹⁰ cм⁻³ при збудженні кільватерного поля в напіввідкритому хвилеводі і 10¹¹ см⁻³ – у плазмовому резонаторі.